The effects of neighborhood socioeconomic status on ADL/IADL among Chinese older adults-neighborhood environments as mediators - Tan, Xiaoshuang; Zhang, Hong; Ren, Xiaohui (Frontiers in Public Health, 2024)
Background: There have been few consistencies in the effects and pathways of neighborhood socioeconomic status(SES) on functional limitations. This study aimed to investigate whether neighborhood socioeconomic status influences ADL/IADL in older residents in China through the neighborhood built environment and social environment. Methods: ADL/IADL were assessed in a sample of 5,887 Chinese individuals aged 60 or older, utilizing data obtained from the 2011 China Health and Retirement Longitudinal Study (CHARLS 2011). Neighborhood SES was measured by the neighborhood per-capita net income. Neighborhood built environment was measured by the security resources, motion resources, living resources, service resources for older adults, and medical resources of neighborhood. Neighborhood social environment was measured by the organizations, unemployment subsidies, minimum living allowance, subsidies to persons older than 65, and pensions to persons older than 80 of the neighborhood. The two-level logistical regression model and multilevel structural equation model (MSEM) were used. Results: The rate of ADL/IADL loss among Chinese older adults aged 60 and above in 2011 were 32.17% and 36.87%, respectively. Neighborhood SES was significantly associated with ADL/IADL in older adults. Compared with the respondents living in communities with lower SES, those living in communities with higher SES possessed better ADL (β = -0.33, P < 0.05) and IADL (β = -0.36, P < 0.05) status. The path of neighborhood socioeconomic status on ADL was completely mediated by the neighborhood built environment (β = -0.110, P < 0.05) and neighborhood social environment (β = -0.091, P < 0.05). Additionally, the effect of neighborhood socioeconomic status on IADL was fully mediated by the neighborhood built environment (β = -0.082, P < 0.05) and neighborhood social environment (β = -0.077, P < 0.05). Conclusions: Neighborhood SES was significantly correlated with ADL/IADL through the neighborhood environment. Improving the ADL/IADL status of older adults residing in low socioeconomic neighborhoods requires enhancing the built and social environment by provisioning additional neighborhood resources.